Skeletal muscle necrosis and regeneration after injection of Thalassophryne nattereri (niquim) fish venom in mice - Lopes Ferreira, Mónica (2001)
Stings by Thalassophryne nattereri are responsible for envenomation of fishermen in north-eastern Brazil. Its venom induces prominent local tissue damage, characterized by pain, oedema and necrosis. The pathogenesis of acute muscle damage induced by T. nattereri venom was studied in mice. Intramuscular injection induced myonecrosis within the first hours. Some muscle cells presented a hypercontracted morphology, but most necrotic fibres were not hypercontracted, being instead characterized by a disorganization of myofibrils, with Z line loss, mitochondrial swelling and sarcolemmal disruption. In addition, thrombosis was observed histologically in venules and veins, together with vascular congestion and stasis, evidenced by intravital microscopy. Venom induced a rapid increment in serum creatine kinase (CK) levels, concomitant with a reduction in gastrocnemius muscle CK activity, whereas no increments in muscle lactic acid were detected. A rapid cytolytic effect was induced by the venom on C2C12 murine myoblasts in culture. The inflammatory reaction in affected muscle was characterized by oedema and scarce cellular infiltrate of polymorphonuclear leucocytes and macrophages, with a consequent delay in the removal of necrotic material. Skeletal muscle regeneration was partially impaired, as evidenced by the presence of regenerating fibres of variable size and by the increase of fibrotic tissue in endomysium and perimysium. It is suggested that T. nattereri venom affects muscle fibres by a direct cytotoxic effect, and that the vascular alterations described preclude a successful regenerative process.